Risk Mitigation Analysis of the Apple Juice Drink Supply Chain - Arwani, Muhammad; Choirun, Annisa'u; Firdausyi, Izzati Ardhan; Bisma, Auditya (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
The problem is that apple productivity in Batu City decreases every year, while the demand for apple juice is increasing along with the increase in tourists and destinations in Batu City. The level of dependence and complexity in the supply chain makes the supply chain as a whole more vulnerable to disruption. Therefore, risk mitigation is needed so that it can reduce and overcome various risks that occur in supply chain institutions. This research aims to identify risk factors and formulate appropriate strategies so that they can be implemented by apple cider supply chain actors. Data analysis uses Fuzzy FMEA (Failure Mode and Effect Analysis) to identify problems or causes of failures that occur. The research results show that the highest risk for farmers is the risk of apples being damaged during the planting process due to pests and climate, with an FRPN value of 5.228; Meanwhile, for the middleman, it can be seen that the highest risk is the risk of late delivery to the factory with an FRPN value of 4.986; and the highest risk in the processing industry is the risk that the quality of the fruit juice product does not comply with the FRPN value of 6.047. Alternative risk mitigation strategies for farmers include increasing harvest area, increasing farmer awareness of good planting methods, using organic fertilizer, and scheduling deliveries. Alternative risk mitigation strategies for middlemen include production scheduling, sorting, grading, using safe transportation packaging, and GHP training. On the part of the processing industry, alternative strategies that can be implemented are increasing the availability of raw materials, reducing the occurrence of product defects, repairing and replacing machine components, and consistent implementation of SOPs.